Pulavar Iḷaṅkaruyiṟaiyanāriṉ Śrī Vācavi avatāramum Àriya Vaiciyar varalārum : kōtravivaraṅkaḷum karuttōviyankaḷum - Iḷaṅkaruyiṟai (Kiṭaikkumiṭam, T. Tācappa Ceṭṭiyār, 1981)
Social history and contemporary socioeconomic conditions of vaisyas in Tamil Nadu.